Strategic Human Resource Management Practices and Organizational Innovation: Evidence from Small and Medium Enterprises in India - Kapoor, Radha (International Journal of Strategic Management, 2024)
Purpose: The aim of the study was to investigate the strategic human resource management practices and organizational innovation: evidence from small and medium enterprises in India. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Research on SHRM practices and organizational innovation in Indian SMEs indicates a positive relationship between SHRM adoption and innovation outcomes. Training initiatives are particularly vital, enhancing innovation capabilities by building human capital. Additionally, fostering a supportive organizational culture promotes creativity and experimentation. Aligning HRM strategies with organizational goals and promoting continuous learning further enhances innovation performance. Overall, SHRM practices play a critical role in driving innovation and competitive advantage in Indian SMEs (Agarwal & Yadav, 2018). Unique Contribution to Theory, Practice and Policy: Resource-based view (RBV) theory, social exchange theory & dynamic capabilities theory may be used to anchor future studies on the strategic human resource management practices and organizational innovation: evidence from small and medium enterprises in India. Develop tailored HRM training programs for SMEs in India, focusing on building capabilities related to creativity, problem-solving, and innovation among employees. Advocate for government policies that promote investment in human capital development and innovation capabilities among SMEs.